Driver subjective feedback study during crosswind gusts on driving simulator for high speed straight line driving - Garje Mohankumar, Anup; Sawanth, Sai Kishan (My University, 2022)
The passenger vehicle industry develops aerodynamic designs that have low drag to improve vehicle efficiency at high speeds. The low drag aerodynamic design affects crosswind stability during straight line driving, this is crucial for passengers and other road user safety. The thesis work subjectively evaluates vehicle high-speed stability under crosswind gusts on VI grade DIM 250 moving platform 6 DOF driving simulator. The simulator allowed testing the high speed response of a high-fidelity vehicle model with groups of drivers in a controlled virtual environment. Initial CAE work focuses on the complexity of SUV vehicle models and the implementation of crosswind gusts in the desktop CAE simulation and driving simulator, coupling between aerodynamics and vehicle dynamics. Stochastic crosswind gust tests were designed on Matlab & Simulink and implemented on CarRealTime vehicle dynamics model on the driving simulator that simulated the change in aerodynamic flow conditions and resulting vehicle aerodynamic forces and moments. Driving clinic is conducted to find the correlation between driver subjective feedback and vehicle’s objective metric response. The vehicle crosswind sensitivity is evaluated using a developed proxy measure. Finally, through statistical tests the study found that the subjective instability feeling is triggered by the vehicle change in lateral and centripetal accelerations response amongst the experienced driver and steering torque demand for common drivers during straight line driving at high speeds under aerodynamic crosswind gusts. The implementation of crosswind gusts on driving simulator is evaluated subjectively.
Keywords: aerodynamics; crosswinds; high Speed; driver-in-loop; correlation; objective metrics; subjective assessment; driver sensitivity